Problems of Criminal Liability of Political Parties in Corruption Offences - Hakim, Lukman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This paper discusses the problems in criminal liability that can then be given criminal penalties against political parties suspected of committing corruption through their representatives as political party administrators and figures affiliated with political parties that commit corruption. Even though the existing legislation is sufficient as a basis for holding political parties accountable for committing acts of corruption, there are ideological problems and problems of legal application that until now, especially after the reformation, there has not been a single political party that can be held criminally responsible for it. This research uses normative legal research. The problem approaches used in this research include the statute, conceptual, and case approaches.